A feasible process for recycling anthocyanins and pectin from the waste peels of purple passion fruit (Passiflora edulis Sims) as food additives - Thanh Tuan Tran; Anh Tu Nguyen; Thi Ngoc Huong Le; Thi Tu Ngan Dinh; Truong Ngoc Mai Ngo; Thi Bich Thuyen Nguyen; Quoc Phong Ho; Van Hong Thien Doan; Viet Nhan Hoa Nguyen (CTU Journal of Innovation and Sustainable Development)
Purple passion fruit is widely cultivated in Vietnam and its peels are considered by-products or agricultural waste after processing, which could cause environmental issues. Notably, these peels contain some valuable components with high bioactivities and applicability, such as anthocyanins (natural colorants) and pectin. Therefore, this work proposes a process for the sequential recycling of anthocyanins and pectin from purple passion fruit waste, in which anthocyanin extraction conditions and their bioactivity by ultrasound-assisted solvent extraction were studied and the characteristics of the obtained pectin were analyzed. The results showed that approximately 95% anthocyanins (125.4 mg/100 g dried peels) were extracted under the best conditions such as 80% ethanol (v/v), 1:25 (g/mL) solid/liquid ratio, 40°C incubation temperature, and 10 minutes sonication time. The findings demonstrated the antioxidant and cytotoxic activity of KB epithelial cells of the anthocyanin extract. Additionally, 7.47% of pectin from the residues after extraction anthocyanins were extracted by citric acid with pH 2 at 87°C for 90 minutes. The pectin has 68.34% purity, and 57.14% of DE, and its structure was confirmed by FT-IR spectra. This study can be utilized to recover useful components from purple passion fruit peel waste, improving the fruit’s value and reducing the environmental impacts of its peels.